Reconciling security and care in digital medicine - Chiara Carboni; Celia Brightwell; Orit Halpern; Oscar Freyer; Stephen Gilbert (npj Digital Medicine)
Abstract Common approaches to cybersecurity frame end users as the weakest link in a system. In this Perspective, we argue that appraising end users as contributors to security can help reconcile both security and care practices. Through two case studies, including Swedish hospitals and a UK smart-home system, we demonstrate the gaps between established security protocols and the daily reality of care practices, and outline approaches to reconcile security and care.